BERAKHIRNYA HAK GUNA BANGUNAN YANG MASIH MENJADI JAMINAN KREDIT DDENGAN HAK TANGGUNGAN - Lismawati Lismawati (Universitas Sriwijaya, 2016)
In the credit required a guarantee for the debt repayment and the Bank is one of the distributor of funds in the form of credit. Guarantee of debt repayment is usually in the form of certificate of land right. One is the land right is certificate of buildings right that have validity period. Expiration of buildings rights that were pledged as collateral for loans with mortgage would have the legal consequence of the existence of a security interest. In Article 18, paragraph 1, letter d Act Mortgage one of which led to the mortgage abolition is the abolishment of land rights. In this research the authors uses the normative research approach based on legislation and conceptual approaches. Data collection techniques with library materials and interviews and also the techniques conclusion with the deductive method. Results of research on the problems that the expiry of building rights as the object of credit guarantees stipulated in Law Number 4 of 1996 on the rights of dependents, the Indonesian Government Regulation Number 40 of 1996 on the right to cultivate (Mortgage), building rights and rights of use, the Regulation of the Minister of Agrarian / Head of the National Land Agency of the Republic of Indonesia Number 5 of 1998 on changes to building rights or the right to use the land burdened residential security rights into property rights and the legal arrangements for the termination of the buildings right is still the object of credit guarantees in the form of Mortgage while the Credit Agreement is not over yet set in the legislation, background Bank provides loans with building rights as the object of loan collateral that are from yuridical and business considerations, the law efforts that can be done of creditors as the holder of a security interest if the right to build an end that is making the promises in the Deed Granting Mortgage, requesting additional collateral, extension of rights, the right change and renewal of building rights. Keywords : Guarantee, Building Rights, Mortgage